Volume 7A: Fluids Engineering Systems and Technologies 2015
DOI: 10.1115/imece2015-50756
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Effect of Impeller Side Clearance on the Centrifugal Pump Performance Using CFD

Abstract: Centrifugal pumps (CP) are probably among the most often used machinery in industrial facilities as well as in common practice. Compared to other types of rotating pumps, CP yield higher efficiency. In aerospace application reducing the weight of the CP impeller has the advantage of reducing mechanical stresses and enable using the CP at high number of revolution. In order to minimize the impeller weight the requirements to study and develop the CP with semi-open impeller appears. Using this type of impeller r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…Practical demonstrations regardinf how the clearance influences performance and efficiency of hydraulic machines can be found in [12][13][14]. Aly et al [12] proved the trend of how the characteristic of the centrifugal pump is shifted for different values of clearances.…”
Section: Sidewall Gaps Of Hydraulic Machinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Practical demonstrations regardinf how the clearance influences performance and efficiency of hydraulic machines can be found in [12][13][14]. Aly et al [12] proved the trend of how the characteristic of the centrifugal pump is shifted for different values of clearances.…”
Section: Sidewall Gaps Of Hydraulic Machinesmentioning
confidence: 99%
“…Practical demonstrations regardinf how the clearance influences performance and efficiency of hydraulic machines can be found in [12][13][14]. Aly et al [12] proved the trend of how the characteristic of the centrifugal pump is shifted for different values of clearances. With increasing side clearance, the head and efficiency decreases and the optimum are in lower flow rates, as can be seen in Figure 2.…”
Section: Sidewall Gaps Of Hydraulic Machinesmentioning
confidence: 99%
“…They observed that the presence of balance holes not only reduced the axial force but also the head developed and efficiency. Ayad et al 36 studied the impact of variation of sidewall clearance gap on the performance characteristics of a centrifugal pump. They found that, with an increase in the clearance gap, the performance dropped as the secondary flow due to the sidewall clearances interferes with the main flow and retards it causing a lower pressure rise.…”
Section: Introductionmentioning
confidence: 99%
“…The issues related to the distribution of pressure in the turbomachinery near-impeller space are thoroughly discussed in reference literature. In the case of pumps, the problem involves analysing axial thrust characteristics (Bhatia 2014;Dong and Chu 2016a, b;Gantar et al 2002;Golovin et al 1989;Godbole et al 2012;Hong et al 2013;Iino et al 1980;Jedral 2001;Kalinichenko and Suprun 2012;Karaskiewicz 2013;Kim and Palazzolo 2016;Lefor et al 2015;Lugova et al 2014;Matsui and Mugiyama 2009;Piesche 1989;Rohatgi and Reshotko 1974;Shimura et al 2012;Wang et al 2013;Wilk 2003bWilk , 2009Zhou et al 2013) or volume losses resulting from untight sealing (Ayad et al 2016;Bhatia 2014;Cao et al 2015;Gantar et al 2002;Kim and Palazzolo 2016;Lefor et al 2015;Liu et al 2016;Shimura et al 2012;Torabi and Nourbakhsh 2016;Wang et al 2016;Wilk and Wilk 2001). So far, experimental (Ayad et al 2016;Dong and Chu 2016b;Gantar et al 2002;Godbole et al 2012;Hong et al 2013;Iino et al 1980;Lefor et al 2015;Nemd...…”
Section: Introductionmentioning
confidence: 99%
“…So far, experimental (Ayad et al 2016;Dong and Chu 2016b;Gantar et al 2002;Godbole et al 2012;Hong et al 2013;Iino et al 1980;Lefor et al 2015;Nemdili and Hellmann 2007;Owen and Pincombe 1980;Piesche 1989;Wilk and Wilk 1996b;Wilk 2008;Zhou et al 2013) and computational (Ayad et al 2016;Cao et al 2015Cao et al , 2016Dong and Chu 2016b;Dykas and Wilk 2008;Golovin et al 1989;Hong et al 2013;Karaskiewicz 2013;Kim and Palazzolo 2016;Lefor et al 2015;Liu et al 2016;Matsui and Mugiyama 2009;Piesche 1989;Rohatgi and Reshotko 1974;Shimura et al 2012;Torabi and Nourbakhsh 2016;Watanabe et al 2016;Zhou et al 2013) tests have been carried out. Selected works are devoted to cases of the centripetal or centrifugal flow (Ayad et al 2016;Bhatia 2014;Cao et al 2015;Dong and Chu 2016a;Gantar et al 2002;Golovin et al 1989;Iino et al 1980;Karaskiewicz 2013;Lefor et al 2015;Liu et al 2016;…”
Section: Introductionmentioning
confidence: 99%